Understanding family dynasty: Nurturing the corporate identity across generations - Juha Kansikas; Mikhail Nemilentsev (International Journal of Business Science & Applied Management (IJBSAM), 2010)
This study aims to analyse the Ahlstrom annual reports. The content analysis contributes to family business corporate identity. According to the results family business corporate identity is based both on history and on the future. Human resource management, customer relationships, high quality, and also family ownership reflect corporate identity in large family corporations. Modern family business corporate identity is based on continuously developing the business concept and its core competency. Meeting the needs of customers and technical quality standards combined with upgrading and developing the business idea characterises family business corporate identity.
Keywords: 650; corporate identity; family business; annual reports; content analysis